Evaluation of the Knowledge and Behavior of Indonesian Mothers about Infantile Colic - Hegar, Badriul (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2024)
Introduction: Infantile colic is a functional gastrointestinal disorder (GSCF) found in 20-30% of infants aged 5 months which is characterized by recurrent prolonged periods of infant irritability, fussing, or crying without obvious cause and cannot be prevented or resolved by parents. Infantile colic is often associated with higher mothers depression and lower quality of life. Mothers' knowledge and behavior of infantile colic varies greatly. This research to investigate the knowledge and behavior of Indonesian mothers regarding infantile colic and related factorMethods: A cross-sectional analytic observational study with the target of 100 mothers with babies aged 0-12 months was performed using an electronic questionnaire in Google forms. The questionnaire consists of multiple-choice questions regarding the mothers' knowledge and behavioral to infantile colic.Results: As many as 82% of mothers understand that infantile colic as recurrent prolonged periods of crying that occur without obvious cause and cannot be prevented or resolved by parents, however only 12% of mothers know that most infantile colic will disappear by the age of 5 months. Forty percent mothers had babies with infantile colic; 97.5% of them were worried about their baby's condition and 7.5% of the mothers gave them medication. There was no significant difference between mothers' age and number of children with inadequate mother-infant interaction (P = 0.770 and P = 0.647)Conclusion: The knowledge and behavior of mothers in Indonesia regarding infantile colic is quite good, however parental reassurance still needs to be improved, especially to reduce maternal anxiety.